Behaviour of glass fiber reinforced polymer concrete beams strengthened with carbon fiber reinforced polymer plate - Salleh, Norhafizah (2021)
The use of fiber-reinforced polymer (FRP) bars in reinforced concrete (RC) structures has emerged as an alternative to traditional RC due to the corrosion of steel in aggressive environments. FRP materials are non-corrosive, non-conductive, lightweight and possess high longitudinal tensile strength, which are advantageous for their use in civil infrastructure. Among the many of FRP available, Glass Fibre Reinforced Polymer (GFRP) appears to be the most affordable compared to other FRP such as Carbon Fibre Reinforced Polymer (CFRP) and Aramid Fibre Reinforced Polymer (AFRP). However, it has been reported that concrete beam reinforced with longitudinal GFRP reinforcement exhibit large deflection due to low modulus of elasticity of the GFRP bars. There is still lack of information on repairing or strengthening of GFRP reinforced concrete beams problem due to larger deflection compared to conventional reinforced concrete beam. In addition, only limited studies numbers reported the contribution of strengthening method in preventing large deformation of GFRP reinforced concrete beams. Most of previous studies were focusing on the use of ordinary reinforced concrete beams (with steel bars) strengthened with CFRP plates. Strengthened concrete beams reinforced with conventional steel reinforcement behave differently than beams reinforced with GFRP reinforcement, in such that the steel reinforcement usually yield before GFRP rupture. Thus, in this study the investigation on the behaviour and performance of GFRP reinforced concrete beam strengthened with CFRP plate was carried out. The effects of the specific properties and characteristics of CFRP plate on the performance of the beams was also studied. In addition, the development of analytical modelling was conducted to predict the optimum CFRP plate bond length and Nominal Moment Capacity in strengthening of GFRP reinforced concrete beams. The study comprised of experimental work, analytical investigation and numerical modelling. This study involved two design conditions of in total ten reinforced concrete beams which is over reinforced design (OR) and under reinforced design (UR). Two reinforced concrete beams reinforced with steel bar (control beam), two reinforced concrete beams with GFRP reinforcement and six GFRP reinforced concrete beams strengthened with different bond length of CFRP plate were tested. Analytical study using Finite Element Analysis (FEA) was used to simulate and verified the experimental data and parametric study. This parametric study was involved the variation of geometrical of CFRP plate in different length. The results from the test show that beam reinforced with GFRP bar resulted in higher flexural load in both conditions of design OR and UR compared to steel reinforced concrete beam with increasing of flexural load by 31.8% to 47.17%, respectively. However, GFRP reinforced concrete beams exhibit greater deflection due to its low modulus of elasticity compared to steel reinforced concrete beams. GFRP reinforced concrete beam strengthened with CFRP plate recorded a good performance in terms of ultimate load and deflection although having a CFRP plate bond length ratio between 0.53 up to 0.96. Result from Finite Element Analysis also showed the same trend behaviour of GFRP reinforced concrete beams strengthened with CFRP plate with experimental results. Results from parametric study obtained the optimum CFRP plate bond length ratio for GFRP reinforced concrete beams strengthened with CFRP plate is 0.83. Additionally, the new equation predicted the Nominal Moment Capacity of GFRP reinforced concrete beam strengthened with CFRP plate well. Using the developed equation, the predicted results were in good agreement in predicting the nominal strength of strengthened beams with mean ratio of the test results to predicted results about 1.07.